The Effect of Earnings Management, Firm Size and Profitability on Tax Avoidance In Automotive Sub-Sector Companies Listed on The Idx For The Period 2017 – 2021 - Indar Kholifatul Sholikhah; Putri Zanufa Sari (NAROTAMA UNIVERSITY, Indonesia, 2023)
This study aims to determine and analyze the effect of earnings management, firm size and profitability on tax avoidance. The population in this study were all automotive sub-sector companies listed on the Indonesia Stock Exchange for the period 2017 – 2021, using a sample of 50. This type of research is quantitative using an exploratory survey method. Methods of data analysis using descriptive test, classical assumption test, multiple linear regression analysis test, and hypothesis testing. The sample data analyzed is secondary data, which will be processed using the SPSS application. From the results of the tests that have been carried out in this study, it can be concluded that earnings management and profitability partially affect tax avoidance, while firm size partially does not affect tax avoidance. However, simultaneously earnings management, firm size and profitability affect tax avoidance.